Variation in quantitative vessel element features of Juglans regia wood in the western Black Sea region of Turkey - Yaman, Barbaros; Yaman, Barbaros (Colegio Postgraduados, 2008)
Variations in quantitative vessel element characters of Juglans regia L. wood were studied in relation to altitude and growth-ring width. Multiple regression analysis using altitude and growth-ring width as independent variables were performed. Significant correlations were obtained for tangential vessel and radial vessel diameter (p <= 0.001), vulnerability ratio and xeromorphy ratio (p <= 0.01), and for the number of vessels per group (p <= 0.05). Vessel frequency is not correlated with independent variables. Non-anatomical factors (altitude and growth-ring width) explain 40.4-80.4% of variation for dependent variables.
Keywords: Juglans Regia; Altitude; Ecology; Growth-Rings; Wood Anatomy